PERBAIKAN TANAH LEMPUNG BERKAPUR DENGAN ABU SEKAM PADI - Suryadharma, Hendra; Hatmoko, John Tri (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2020)
At the research area, there was found the high content lime -clay, that is usually low plasticity clay. The purpose of this research, then, to improve engineering properties of high content lime-clay by addition of rice husk ash (RHA). To enhance the purpose, a series of experimental programs was undertaken. Firstly, the standard compaction test was done on the soil + lime with and without curing time. Secondly, to get optimum lime content, there was performed CBR and unconfined compression tests on the soil +lime, and it was found that optimum lime content is 4%. Then, the CBR and unconfined compression experiment were done on the soil + 4% lime + ( 5, 10, 15,20, 25%) of RHA with 7,21,28, 36  56 days curing time. The results indicate that there was no significant changes of optimum moisture content (OMC) and maximum dry density (MDD) due to addition of lime to the soil. The initial unconfined compression stress of soil sample was 41.5 kPa that is classified as soft clay. Due to addition of lime, there was significant improvement of CBR and unconfined compression stress on 4% of lime with 36 days curing period. The CBR value and unconfined compression stress on the soil + lime + RHA increase proportional to the proportion of RHA. With respect to curing time, there was the improvement of the CBR and unconfined compression stress of stabilized soil, and the significant improvement was found on 56 days curing time. However, there was no optimum curing time found in this research..